SAT0559 IMPACT OF BLOCK SWITCH TO BIOSIMILAR ETANERCEPT IN PRACTICE – AN EXPERIENCE FROM ONE TERTIARY RHEUMATOLOGY DEPARTMENT. (June 2019) - Brites, Luisa; Costa, Flavio; Freitas, João Dinis de; Luis, Mariana; Coutinho, Margarida; Santiago, Mariana; Salvador, Maria Joao; Duarte, Catia; José Antonio, P; Silva, Da
Abstract : Background: Biosimilars of biotechnological agents represent an important opportunity to increase accessibility to these medications. Clinicians still maintain reservations regarding the similarity of their efficacy and safety in practice. Objectives: To evaluate the clinical consequences of a non-medical switch of etanercept (ETN) original to biosimilar in a clinical practice setting. Methods: The study included all patients aged 18+ treated in a Tertiary Rheumatology Department with original ETN who were switched to his biosimilar following a decison by the hospital administration, accepted by rheumatologists. Patients were informed of the switch prior to its occurrence, in simple terms underlining the similarity in terms of regulatory issues and scientific evidence. Disease activity, adverse events and adaptation to the drug delivery system were evaluated at each visit. Disease activity at baseline (time of switch), 3 and 6 months after was compared using Paired samples T-test or Wilcoxon test as adequate. A p≤0.05 was considered statistically significant. Continuous variables are presented as means and categorical variables as proportions. Results: From 98 patients treated with original ETN in our department, 89 were switched to his biosimilar. The remaining ones maintained the treatment with the reference biological product for several reasons. Eight patients were excluded from this analysis due to poor adherence to treatment (n=4) and early interruption of treatment [n=4: due to surgery (n=1), respiratory infection (n=1), suspected allergic reaction to biosimilar (n=1) and own initiative (n=1)]. Of the remaining 81 patients (58% female, mean age 56.2±12.1 years), 38.3% had RA, 40.7% SpA, 18.5% PsA and 2.5% JIA. Disease activity was stable over the follow up in patients with RA, PsA and SpA as no statistically significant differences were observed in acute phase reactants, patient or physician global assessment between the three time points. Minor adverse events were reported by 2 patients (pain and local cutaneous reaction), 2 reported sense of disease exacerbation in the first three months that was not confirmed by clinical and analytical evaluation and 2 patients reported minor infections. Good adaptation to the drug delivery instrument was reported by 93.8% of patients (n=76). Conclusion: The switch from ETN to his biosimilar in this group of patients followed in routine care did not affect the overall efficacy and safety of treatment. We did not observe a significant impact of nocebo effect. Disclosure of Interests: None declared